Political Will and Strategic Planning in the Implementation of Universal Basic Education in Nigeria: The Obafemi Awolowo Example - Aboluwodi, Akinjide (Journal of Education and Research, 2015)
In Nigeria, the introduction of Universal Basic Education is meant to reduce the problem of illiteracy, ignorance and poverty to the barest level; a goal it shares with the goals of the World Conference on Education For All. It is meant to aid rapid national economic and political development. Its implementation has become a major challenge; hence its success has been marginal across the country. Among the factors identified as hindering its success are lack of political will on the part of government, absence of strategic planning, inaccurate data, politicisation of the programme and improper funding. Back in 1955, the then Prime Minister in Western Nigeria1 Obafemi Awolowo introduced a similar programme, Universal Primary Education with strong commitment and determination. The same commitment, determination and political will that helped Awolowo meet the objectives of his programme are what the government can apply to sustain and advance the current Universal Basic Education programme.